Peran Human Capital Strategy dan Kepemimpinan Adaptif terhadap Ketahanan Organisasi: Studi Empiris pada PT PLN (Persero) - Muhammad Nashhan Ridwanto; Adjie Arya Sena; Rony Edward Utama (Jurnal Ilmiah Manajemen dan Kewirausahaan, 2025)
This study aims to analyze the role of human capital strategy and adaptive leadership in strengthening organizational resilience at PT PLN (Persero), one of Indonesia's key state-owned enterprises. Amidst global challenges such as digital transformation, energy transition, and post-pandemic dynamics, the need for superior human resources and responsive leadership is increasingly critical. Using a descriptive qualitative approach, data were collected through literature studies, internal documents, and supported by relevant empirical findings. The results indicate that the integration of competency-based HR strategies and adaptive leadership significantly enhances organizational resilience to disruption. Strategies such as succession planning, digital learning, and collaborative culture have proven effective in boosting flexibility and innovation. The study provides practical implications to reinforce HR's role in PLN’s strategic transformation process in facing uncertainty.